Pengaruh Pemberian Sanksi terhadap Disiplin dan Motivasi Kerja Pegawai Organisasi Perangkat Daerah (OPD) Kabupaten Lombok Barat - Harun Arrasyid; Hermanto Hermanto; Sri Wahyulina (Journal on Education, 2022)
In an organization, employee discipline is crucial for carrying out work effectively, especially in determining the direction and goals of the organization. The purpose of this research is to directly examine the influence of sanctions on work motivation, the influence of work motivation on employee discipline, the influence of sanctions on work discipline, and the influence of sanctions on employee discipline in the Regional Government Agencies (OPD) in West Lombok Regency through work motivation. The research method used is quantitative research with a population of 712 civil servant employees from 10 OPD in West Lombok Regency, and a sample size of 100 civil servant employees using the Slovin formula and purposive sampling technique. The data analysis used is Partial Least Square-Structural Equation Model (PLS-SEM). The research results show significant direct effects between the imposition of sanctions and work motivation, work motivation and employee discipline, the imposition of sanctions and work discipline, and the imposition of sanctions on employee discipline in the OPD in West Lombok Regency through work motivation.